Hubungan Literasi Visual dengan Computational Thinking Peserta Didik Kelas V Sekolah Dasar Se-Kecamatan Argomulyo - Adelia Bella Citra; Roy Ardiansyah (Universitas Sebelas Maret, 2025)
This study aims to determine the relationship between visual literacy and computational thinking among fifth-grade elementary school students in Argomulyo District. Visual literacy refers to students' ability to understand, interpret, and communicate information through visual media, while computational thinking refers to the ability to think logically, systematically, and structurally in solving problems. This study uses a quantitative approach with a correlational method. The population in this study was all fifth-grade students from various elementary schools in the Argomulyo subdistrict, and the sample consisted of fifth-grade students at SDN Cebongan 03, SDN Noborejo 01, SDN Randuacir 02, and SDN Randuacir 03. The sampling technique used was stratified random sampling. Data collection was conducted using an essay-type test. The instruments used were questionnaires and tests that had been validated by experts. The validation techniques used included validity tests and reliability tests. Data analysis techniques used prerequisite analysis tests, namely normality and linearity tests, followed by hypothesis testing using simple correlation tests. The results of this study show that visual literacy and computational thinking have a positive and significant relationship that can be explained through the interconnection between visual literacy and computational thinking. The data analysis results indicate a significant relationship between visual literacy and computational thinking, as evidenced by a significance level of <0.05. This finding suggests that the higher the visual literacy skills of students, the better their computational thinking abilities. Therefore, developing learning that effectively integrates visual elements can be a strategy to enhance students' computational thinking skills at the elementary school level.